Effectiveness Of Political Party Financial Assistance Program On Political Education For Political Party Cadres In Riau Islands Province - Ikhsan Yuditra Usman; Edy Akhyary; Fitri Kurnianingsih (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2025)
The phenomenon of this research is to see the financial assistance channeled to political parties, especially in the Riau Islands Province towards the implementation of Political Education for their respective Political Party Cadres. According to the Indonesian Democracy Index (IDI), in 2022-2023 Riau Islands Province in the 22nd indicator, namely